Exchange Rate Regimes and Macroeconomic Stability: The Case of Sweden 1972-1996 - Anders Bergvall (Uppsala University, Department of Economics, 2002)
In this paper I investigate the relevance of the exchange rate regime for macroeconomic stability. I simulate hypothetical macroeconomic developments under different regimes in Sweden during the period 1972 -1996. The main question is how stable output would have been if Sweden had had a floating exchange rate regime. Would it have been better with a floating exchange rate than the actual quasi-fixed regime? Also the development with an irrevocably fixed exchange rate is investigated. The results indicate that the central bank can stabilize much of the macroeconomic disturbances under a floating exchange rate, but still the volatility of the macroeconomic variables under the hypothetical floating exchange rate regime is about the same as under the actual quasi-fixed regime.
Keywords: E52; F31; F41; 330; Exchange rate regimes; macroeconomic stability; monetary policy; Wechselkurssystem; Wirtschaftswachstum; Schweden